Oral carcinoma development after 23 years of renal transplantation - Isabel Schausltz Pereira Faustino; Diego Teztner Fernandes; Alan Roger Santos-Silva; Pablo Agustin Vargas; Marcio Ajudarte Lopes (University of São Paulo, 2019)
Renal transplant patients are treated with immunosuppressive drugs that decrease the effectiveness of the immune system, making them more prone to developing cancer. Skin and lip carcinomas are common malignancies encountered after transplantation, whereas oral carcinomas are rare. We report the case of a 51-year-old female Caucasian patient, with no history of smoking, who presented white lesions on the tongue and an ulcerated lesion on the lower lip beginning 4 months prior. Diagnosis of squamous cell carcinoma for both lesions was made following incisional biopsies. Interestingly, the patient reported a renal transplantation 23 years prior, and was maintained on a combination of cyclosporine, mycophenolate sodium and prednisone. The patient also presented a history of several basal and squamous cell carcinomas on sun-exposed areas of the skin. Both lesions were surgically excised. No sign of recurrence or new lesions in the oral cavity have been observed; however, new skin lesions are frequently diagnosed. This case report highlights that oral cancers may occur in transplant patients in the absence of classical risk factors. Thus, clinicians must be aware of the importance of thorough oral examination in transplant patients in routine follow-up.